Role of CRISPR-Cas system on antibiotic resistance patterns of Enterococcus faecalis - Pourya Gholizadeh; Mohammad Aghazadeh; Reza Ghotaslou; Mohammad Ahangarzadeh Rezaee; Tahereh Pirzadeh; Longzhu Cui; Shinya Watanabe; Hadi Feizi; Hiva Kadkhoda; Hossein Samadi Kafil (BMC, 2021)
Abstract Clustered regularly interspaced short palindromic repeat (CRISPR)-Cas systems are one of the factors which can contribute to limiting the development and evolution of antibiotic resistance in bacteria. There are three genomic loci of CRISPR-Cas in Enterococcus faecalis. In this study, we aimed to assess correlation of the CRISPR-Cas system distribution with the acquisition of antibiotic resistance among E. faecalis isolates. A total of 151 isolates of E. faecalis were collected from urinary tract infections (UTI) and dental-root canal (DRC). All isolates were screened for phenotypic antibiotic resistance. In addition, antibiotic resistance genes and CRISPR loci were screened by using polymerase chain reaction. Genomic background of the isolates was identified by random amplified polymorphic DNA (RAPD)-PCR. The number of multidrug-resistant E. faecalis strains were higher in UTI isolates than in DRC isolates. RAPD-PCR confirmed that genomic background was diverse in UTI and DRC isolates used in this study. CRISPR loci were highly accumulated in gentamycin-, teicoplanin-, erythromycin-, and tetracycline-susceptible strains. In concordance with drug susceptibility, smaller number of CRISPR loci were identified in vanA, tetM, ermB, aac6'-aph(2"), aadE, and ant(6) positive strains. These data indicate a negative correlation between CRISPR-cas loci and antibiotic resistance, as well as, carriage of antibiotic resistant genes in both of UTI and DRC isolates.